Effective Leadership and Supervisory Skills of Principal: Predictors of Job Satisfaction among Public Elementary School Teachers - Beladas, Jean P.; Callo, Eden C. (Future Science / FSH-PH Publications, 2023)
The study's dependent variable is the teacher's compelling desire to know the Degree of job satisfaction in terms of fundamental requirements, self-actualization, supervision, and indicators. Job safety, predictable income, vessel maintenance and equipment, mental stress on the job, your earnings or Pay, cleanliness of the work, hours worked, peace of mind/security, time away from home, healthfulness of the workplace, and physical exhaustion on the job are all necessities. Accountability, productivity, recognition, job challenge, excitement, and undertaking something worthwhile are all components of self-actualization. The study on principals' effective leadership and supervisory abilities as predictors of work satisfaction among teachers in public primary schools seeks to determine whether the two qualities of the principal have anything to do with teachers' passion for their jobs. The study uses additional supporting material to demonstrate the relationship between leadership, supervisory skills, and job happiness. The respondents strongly agreed with the claims about their respective public-school principals' leadership abilities, demonstrated effective supervisory skills in their respective schools, improved those institutions, and produced outstanding students. The findings suggest a strong relationship between teachers' job satisfaction and the principal's leadership abilities. Furthermore, teacher job satisfaction and the effectiveness of the principal's supervision are highly correlated.